Staphylococcus epidermidis, Host Immune Factors and Medical Device Infections - NERISSA THOMAS (2023)
Medical device infections, commonly caused by S. epidermidis are difficult to treat due to the formation of biofilms on the medical device surface which protect S. epidermidis against host immune defences and antibiotics. This project aimed to further our understanding of the interactions between S. epidermidis, and fibroblasts or macrophages in the presence of uncoated or whole-blood coated titanium (Ti) and titanium alloy (TiAlV) discs. S. epidermidis and fibroblasts/macrophages were cocultured on Ti or TiAlV discs for 6 and 24 h. The resulting samples were then analysed in one of three ways, 1) supernatant assayed for fibroblast/macrophage cytokine expression; 2) bacterial RNA extracted to analyse transcription of adhesion and biofilm associated genes; 3) samples prepared for visualisation using confocal microscopy and scanning electron microscopy. Cytokine analysis found increased expression of various cytokines involved in the regulation of immune responses to injury and infection, including IL-1β, MCP-1 and MIP-3α or IL-8, MIF, IFN-γ by macrophages and fibroblasts respectively on uncoated Ti, and IL-1α, IL-6 and TNF-α by fibroblasts on pre-coated Ti. RT-qPCR of S. epidermidis found that gene transcription differed depending on disc or culturing conditions, indicating that both host cells and surfaces influence attachment and biofilm formation. Microscopy showed the adherence of S. epidermidis, macrophages and fibroblasts to discs in monoculture and co-culture, however, by 24 h, fibroblasts detached implying that S. epidermidis impacts the ability of fibroblasts to survive on the discs. To conclude, the results suggest that Ti or TiAlV discs, S. epidermidis and macrophages/fibroblasts interact with and affect each other during the initial stages of infection, with S. epidermidis pathogenesis being further influenced by the presence of host factors. This work is clinically relevant and directly translational to improving the treatment and diagnosis of medical device infections, which remain a burden on the NHS.